Manufacturing method of green compact and manufacturing method of sintered compact
Patent Information
- Application Number
- JP2021548977
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-27
- Filing Date
- 2020-09-24
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2040-09-24
AI Technical Summary
【0018】 この発明の圧粉体の製造方法によれば、凹部を有する圧粉体を冷間等方圧加圧で形成するに当り、芯材の近傍の圧粉体表面への隆起の発生を抑制することができる。
Smart Images

Figure 0007645804000003 
Figure 0007645804000004 
Figure 0007645804000005
Abstract
Description
[Technical field]
[0001] The present invention proposes a technique relating to a method for producing a green compact and a method for producing a sintered compact. [Background technology]
[0002] For example, titanium and titanium alloys are being considered for use in various parts due to certain excellent properties such as fatigue resistance, corrosion resistance, light weight and high specific strength. However, in order to manufacture parts made of titanium or titanium alloys, it is generally necessary to carry out a number of steps, such as melting by electron beam melting or vacuum arc melting, casting, and in some cases, further hot rolling, heat treatment, machining, welding, etc., which increases the manufacturing cost. Due to such high costs, it is difficult to say that the range of applications of titanium-containing materials has been sufficiently expanded.
[0003] Under these circumstances, in recent years, a powder metallurgy method has been attracting attention, in which a titanium-based green compact having a predetermined shape is obtained by filling a titanium-containing raw material powder into a resin mold and subjecting the raw material powder to cold isostatic pressing, as a so-called near-net shape method. Note that in this powder metallurgy method, after the cold isostatic pressing, sintering and / or hot isostatic pressing may be performed as necessary to increase density.
[0004] As a related technology, Patent Document 1 describes "a method for manufacturing a compacted body, in which a rubber mold filled with raw material powder is pressed in one axial direction within a metal mold to form a compact of the raw material powder, characterized in that a portion of the outer surface of the compacted body in a direction approximately perpendicular to the pressing direction is formed by a high-rigidity mold member arranged in the rubber mold." Furthermore, Patent Document 2 proposes "a method for producing a sintered titanium alloy by a powder mixing method, characterized in that instead of titanium powder, a powder obtained by mixing titanium powder, (Ti-H) alloy powder, and titanium hydride powder in a mass ratio of hydrogen to titanium of 0.002 or more and less than 0.030 is used as the raw material powder." The powder metallurgy method described above is not limited to titanium and titanium alloys, but can be used with various pure metals and alloys. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2001-131605 A [Patent Document 2] Japanese Patent Application Publication No. 6-33165 Summary of the Invention [Problem to be solved by the invention]
[0006] Incidentally, when manufacturing a green compact having a recess such as a through hole or a non-through cavity by powder metallurgy, a core material such as a core may be placed in a resin mold at a location corresponding to the recess, and cold isostatic pressing may be performed on the raw material powder filled in the mold. Patent Document 1 uses a high-rigidity core, which is a cylindrical member made of steel, as such a core material (see paragraph 0035).
[0007] However, when a high-rigidity core made of metal such as steel as described in Patent Document 1 is used, there is a problem in that the surface of the green compact obtained after cold isostatic pressing that is located in the vicinity of the high-rigidity core is raised, and the green compact is not formed into a desired shape.
[0008] An object of the present invention is to provide a method for producing a powder compact and a method for producing a sintered body that can suppress the occurrence of protrusions on the powder compact surface in the vicinity of a core material when forming a powder compact having recesses by cold isostatic pressing. [Means for solving the problem]
[0009] As a result of intensive research, the inventors have found that the occurrence of protrusions on the surface of the green compact can be suppressed by using a resin core material together with a resin mold in cold isostatic pressing. The reason for this is believed to be as follows. When a resin core material is used, the resin core material elastically deforms during pressing, appropriately transmitting pressure to the raw material powder, and the entire raw material powder, including the area around the core material, is sufficiently compacted. In addition, after unloading, the resin core material returns to its original state so as to come out of the recess, and does not adversely affect the green compact. It is presumed that this makes it difficult for partial protrusions to form on the surface of the green compact. However, the present invention is not limited to such a theory.
[0010] Based on the above findings, the method for producing a powder compact of the present invention is a method for producing a metal powder compact having a recess, and includes a step of performing cold isostatic pressing on raw material powder filled in a resin mold with a resin core material having a shape corresponding to the recess positioned in the resin mold at a location corresponding to the recess.
[0011] In the method for producing a powder compact of the present invention, it is preferable to use, as the core material, a core material made of a resin material that has a stress of 0.3 MPa to 3.5 MPa when the strain is 20% in a uniaxial compression test.
[0012] In the method for producing a powder compact of the present invention, it is preferable that the core material contains at least one selected from the group consisting of a silicone resin and a fluororesin.
[0013] In the method for producing a green compact of the present invention, it is preferable to use a mold made of a thermoplastic resin having a Shore D hardness in the range of 30 to 120 as the mold.
[0014] In the method for producing a powder compact of the present invention, cold isostatic pressing can be performed in a state in which the core material, which is a separate member from the mold, is positioned in a portion of the mold corresponding to the recess, with the wall of the mold sandwiched between the core material and the raw material powder.
[0015] Alternatively, in the method for producing a powder compact of the present invention, the mold with which the core material is integrally formed can be used.
[0016] The recess may be a non-through recess. As the above-mentioned green compact, for example, a titanium-based green compact made of titanium or a titanium alloy is produced, or, as the above-mentioned green compact, for example, an iron-based green compact made of iron or an iron alloy can be produced.
[0017] The method for producing a sintered body of the present invention is a method for producing a sintered body, which includes a step of sintering and / or hot isostatic pressing a green compact produced by any of the above-mentioned methods for producing a green compact. Effect of the Invention
[0018] According to the method for producing a green compact of the present invention, when a green compact having recesses is formed by cold isostatic pressing, the occurrence of protrusions on the surface of the green compact in the vicinity of the core material can be suppressed. [Brief description of the drawings]
[0019] [Figure 1] FIG. 2 is a perspective view showing an example of a resin mold that can be used in the method for producing a powder compact according to the embodiment of the present invention. [Diagram 2] 2 is a longitudinal cross-sectional view taken along the central axis of the mold, showing the mold of FIG. 1 together with a core material. [Diagram 3] FIG. 3 is a vertical cross-sectional view showing a titanium-based green compact produced by using the mold and core material of FIG. 2. [Figure 4] FIG. 3 is a vertical cross-sectional view showing a schematic state in which cold isostatic pressing is performed using the mold and core material shown in FIG. 2. [Diagram 5]FIG. 5 is a vertical cross-sectional view showing the titanium-based powder compact obtained by cold isostatic pressing in FIG. 4 in a state before the core material and part of the mold are removed. [Figure 6] FIG. 2 is a vertical cross-sectional view showing a schematic state in which cold isostatic pressing is performed in a method for producing a powder compact using a metal core material. [Figure 7] 7(a) and (b) are vertical cross-sectional views showing other examples of a resin mold and a core material, respectively. [Figure 8] FIG. 11 is a vertical cross-sectional view showing a titanium-based green compact that can be manufactured by using a method for manufacturing a green compact according to another embodiment. [Figure 9] FIG. 1 is a diagram showing modeling data of a 3D printer used in Test Example 1 of the embodiments. [Figure 10] 1 is a photograph of a titanium-based green compact produced in Test Example 2 of the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings. A method for producing a powder compact according to one embodiment of the present invention includes a step of cold isostatically pressing a raw material powder in a mold 1 using a mold 1 and a core material 11 as shown in Figures 1 and 2, to produce a titanium-based powder compact 61 made of titanium or a titanium alloy as shown in Figure 3 or other metallic powder compacts. The term "metallic" as used here includes not only pure metals but also alloys. In the following, a titanium-based powder compact and a titanium-based sintered body will be described in detail as examples of metallic powder compacts and sintered bodies, but each of the configurations described here or a combination thereof can also be applied to the production of other metallic powder compacts and sintered bodies.
[0021] The titanium-based powder compact 61 shown in Fig. 3 has a generally cylindrical shape overall, and has a recess 62 formed in one end face in the axial direction (the lower end face in Fig. 3) that is a hollow cylindrical recess that does not pass through the end face. In order to manufacture the titanium-based powder compact 61 having such a recess 62, the mold 1 used in the cold isostatic pressing has a molding space 2 having a shape corresponding to the shape of the titanium-based powder compact 61.
[0022] More specifically, the mold 1 comprises a cylindrical outer cylinder wall portion 3 having an inner circumferential surface that matches the outer circumferential surface of the titanium-based powder compact 61, an annular wall portion 4 provided at one end (the lower end in FIG. 2) of the outer cylinder wall portion 3, and a cylindrical inner cylinder wall portion 5 with a bottom at its center. The end of the inner cylinder wall portion 5 without a bottom is attached to a hole in the center of the annular wall portion 4, and one end of the outer cylinder wall portion 3 is sealed by the annular wall portion 4 and the inner cylinder wall portion 5.
[0023] Here, in order to resist the pressure received from the raw material powder in the molding space 2 during cold isostatic pressing, a cylindrical core material 11 is inserted into the inner cylindrical wall portion 5 of the mold 1, which forms the recess 62 to be provided in the titanium-based powder compact 61, as shown by the arrow in FIG. 2 .
[0024] Then, raw material powder is filled into the molding space 2 of the mold 1, and the other end (upper end in FIG. 4) of the outer cylindrical wall portion 3 of the mold 1 is sealed with a disk-shaped member 6 as shown in FIG. 4. Cold isostatic pressing (CIP) is performed inside a cold isostatic pressing device (not shown) to indirectly press the raw material powder from outside the mold 1 via the mold 1. Note that here, the disk-shaped member 6 constitutes a part of the mold 1. By the cold isostatic pressing, the raw material powder in the mold 1 is pressed and compacted to become a titanium-based green compact 61.
[0025] The pressure applied to the raw material powder in cold isostatic pressing is, for example, 200 MPa or more, typically 400 MPa or more. The pressure may be, for example, 600 MPa or less, typically 500 MPa or less. The holding time at such a pressure may be, for example, 0.5 minutes to 30 minutes.
[0026] After pressing by cold isostatic pressing, the titanium-based powder compact 61 is removed from the cold isostatic pressing device together with the mold 1 and the core material 11, and the outer cylinder wall 3, the annular wall 4, and the disk-shaped member 6 around the titanium-based powder compact 61 are removed. Thereafter, as shown in Fig. 5, the core material 11 and the inner cylinder wall 5 in the recess 62 of the titanium-based powder compact 61 are removed. The core material 11 may be removed before removing the outer cylinder wall 3, etc. In this manner, the titanium-based powder compact 61 can be manufactured.
[0027] In performing such cold isostatic pressing, if a core material 71 made of metal such as steel is inserted and arranged in the inner cylindrical wall portion 5 of the mold 1 as shown in FIG. 6, the inventors speculate that the following problems occur. In the mold 1 shown in FIG. 6, when the raw material powder in the mold 1 gradually decreases in volume due to the pressing force, the highly rigid metallic core material 71 does not substantially elastically deform. For this reason, if a highly rigid core material 71 is used, the pressing force is not easily transmitted to the raw material powder via the core material 71, and the pressing force may be transmitted in different ways between the portion near the core material 71 and the portion away from the core material 71. In particular, the pressing force is not transmitted in the radial direction of the core material 71, and the pressing force is not sufficiently transmitted to the raw material powder located around the core material 71. As a result, the raw material powder located around the core material 71 is insufficiently compacted compared to the raw material powder on the outer periphery side. In the resulting titanium-based powder compact 81, as shown in an exaggerated manner in FIG. 6, the surface on the annular wall portion 4 side of the mold 1 is raised at the surface portion located around the core material 71 in the vicinity of the core material 71, forming a raised portion 83.
[0028] To deal with this, in this embodiment, a resin core material 11 is used instead of a metal core material 71. When the resin core material 11 is compressed in the axial direction by the pressure acting in the axial direction of the mold 1 during cold isostatic pressing, the core material 11 also transmits the pressure in the radial direction, as shown in FIG. 4. As a result, the raw material powder around the core material 11 is also sufficiently compacted, and the titanium-based compact 61 suppresses the protrusion of the surface portion around the core material 11. Note that the core material 11 can be restored to its original state by protruding from the recess 62 after unloading. Therefore, if the resin core material 11 is used, a titanium-based compact 61 with excellent dimensional accuracy can be manufactured. This is also true when a raw material powder made of a metal other than titanium or a titanium alloy is used to manufacture a metal compact other than the titanium-based compact 61, and a metal compact with excellent dimensional accuracy can be obtained.
[0029] The resin core 11 is preferably made of a resin material that has a stress of 0.3 MPa to 3.5 MPa when strain is 20% in a uniaxial compression test. A core 11 made of a resin material with a stress of 0.3 MPa to 3.5 MPa at 20% strain is compressed more appropriately during cold isostatic pressing, and pressure is more appropriately transmitted to the raw material powder. From this perspective, the core 11 is preferably made of a resin material with a stress of 0.3 to 2.0 MPa at 20% strain, and even more preferably of 0.4 MPa to 0.8 MPa. To measure the stress at 20% strain of the core material 11, a uniaxial pressure is applied to a resin sample of 10 mm diameter x 10 mm height in the height direction at a speed of 1 mm / min, and the stress is measured when the strain of the resin sample (reduction in the height of the resin sample) becomes 20%. For the uniaxial compression test, an Instron 5565 material testing machine can be used.
[0030] Specifically, the core material 11 preferably contains at least one selected from the group consisting of silicone resin, chloroprene resin, and fluororesin, and more preferably contains at least one selected from the group consisting of silicone resin and fluororesin. When the core material 11 contains at least one of these resins, the titanium-based green compact 61 has particularly excellent dimensional accuracy. The core material 11 containing silicone resin or fluororesin can be easily removed from the inner cylindrical wall 5 of the mold 1 after cold isostatic pressing, and is therefore particularly preferred for easy and efficient production of the titanium-based green compact 61. When a silicone sealant is used as the silicone resin, it has the advantage that it is easy to form even a complexly shaped recess 62 with high precision because it is in a gel state or the like and exhibits fluidity when filled into the inner cylindrical wall 5 of the mold 1. When a silicone sealant is used, it is preferable to fill the inner cylindrical wall 5 of the mold 1 with the silicone sealant in a gel state, leave it for a certain period of time to solidify, and then perform cold isostatic pressing. The resin core material 11 may be any material that is inserted or filled into the inner cylinder wall portion 5 and is appropriately compressed during cold isostatic pressing, and that is capable of deforming in a direction that allows it to come out of the recess 62 without affecting the titanium-based powder compact 61 when the load is removed.
[0031] The resin mold 1 is preferably made of a thermoplastic resin, and is particularly preferably made of an acrylic resin, an acrylic resin containing an elastomer, a polylactic acid (PLA) resin, or the like. In order to ensure the required strength and maintain its shape even when filled with raw material powder, the resin mold 1 is preferably made of a thermoplastic resin having a Shore D hardness in the range of 30 to 120, or may be made of a thermoplastic resin having a Shore D hardness in the range of 30 to 85. The Shore D hardness can be measured by a test method conforming to JIS K7215 (1986). From the same viewpoint, the thickness of the resin mold 1 is preferably 0.5 mm to 2.0 mm. The resin mold 1 can be produced by various methods, but it is preferable to use a 3D printer since it allows molds 1 of various shapes to be easily produced.
[0032] When manufacturing a titanium-based sintered body made of titanium or a titanium alloy, the cold isostatic pressing process includes a process of sintering and / or hot isostatic pressing (HIP) the titanium-based compact 61. In the sintering process, the titanium-based compact 61 can be heated for 1 to 3 hours at a temperature of, for example, 1200°C to 1300°C depending on the material of the titanium-based compact 61. In the hot isostatic pressing process, an isostatic pressure of about 100 MPa to 200 MPa can be applied to the titanium-based compact 61 for 30 to 90 minutes at a temperature of, for example, 800°C to 1000°C using a pressure medium such as argon gas. This allows the titanium-based sintered body to be manufactured. In the hot isostatic pressing process, sintering generally proceeds because the process is performed at a high temperature. Therefore, the titanium-based sintered body is also referred to as a titanium-based sintered body here if the titanium-based compact 61 is obtained by performing only hot isostatic pressing. When both sintering and hot isostatic pressing are performed, the order of these steps is not particularly important, but for example, hot isostatic pressing can be performed after sintering.
[0033] The above describes the case where core material 11, which is a separate component from mold 1, is placed in a location within inner cylinder wall 5 of mold 1 that corresponds to recess 62, and cold isostatic pressing is performed in a state in which inner cylinder wall 5, which is the wall of mold 1, is sandwiched between core material 11 and the raw material powder.
[0034] On the other hand, as shown in FIG. 7(a), it is also possible to use a core material 31 formed integrally with the mold 21. More specifically, this mold 21 is provided with a cylindrical core material 31 attached integrally to the center of an annular wall portion 24 provided at one end (lower end portion in FIG. 7) of an outer cylinder wall portion 23. In this example, the portion corresponding to the inner cylinder wall portion 5 in the mold 1 in FIGS. 1 and 2 is also formed of the core material 31 integral with the annular wall portion 24. Even in such a case, by making the core material 31 from a resin, it is possible to suppress the formation of a protruding portion in the titanium-based powder compact, as described above. However, the degree of freedom of the core material's restoration after unloading is superior to the form in which the core material 11 is inserted into the inner cylinder wall portion 5 of the mold 1 as shown in FIGS. 1 and 2.
[0035] Alternatively, as shown in Fig. 7(b), a mold 41 having no portion corresponding to the inner cylindrical wall portion 5 in the mold 1 in Figs. 1 and 2 and a hole portion 44a formed in the center of the annular wall portion 44 may be used, with a cylindrical core material 51 as a separate member inserted into the hole portion 44a, for cold isostatic pressing. In this case, the raw material powder filled in the molding space 42 of the mold 41 comes into direct contact with the core material 51. Even with the mold shown in Fig. 7(b), if the core material 51 is made of resin, the effect of suppressing the bulging of the titanium-based powder compact described above can be obtained.
[0036] The manufacturing method according to the embodiment of the present invention can also manufacture a metallic powder compact such as a titanium-based powder compact 91 having a through-hole-like recess 92 as shown in Fig. 8. This titanium-based powder compact 91 is similar to the titanium-based powder compact 61 shown in Fig. 3, except that the recess 92 is a through-hole that passes through between the end faces in the axial direction. As described above, the recess may be a through hole or a depression having a bottom. The shape of the recess is not limited to a cylindrical shape as shown in the figure, and may be various complex shapes. The number of recesses in the powder compact to be manufactured may be one, or two or more. When the powder compact has two or more recesses, it is preferable that one or more of the recesses are formed by the above-mentioned method to suppress protrusion.
[0037] When a titanium-based compact or titanium-based sintered body is manufactured by the above-mentioned method, various powders such as pure titanium powder, alloy element powder, and master alloy powder can be used as the raw material powder in combination as necessary. The pure titanium powder means a powder consisting essentially of titanium, the alloy element powder means a powder containing only an alloy element such as a titanium alloy, and the master alloy powder means a powder containing a plurality of alloy elements. The raw material powder can be, for example, only pure titanium powder, or it can be a mixture of pure titanium powder and one alloy element powder selected from the group consisting of iron, aluminum, vanadium, zirconium, tin, molybdenum, copper, and nickel and / or two or more master alloy powders thereof. Alternatively, a powder containing titanium and an alloy element can be used as the raw material powder. Note that pure titanium means titanium with a titanium content of 99% by mass or more. The mass ratio of metals in the raw material powder can be titanium:alloy element=100:0 to 75:25, or titanium:alloy element=90:10. When producing a green compact made of a metal other than titanium or a titanium alloy, a raw material powder of a material suitable for the metal is used. For example, when producing an iron-based green compact made of pure iron or an iron alloy, the raw powder can be pure iron powder, and further, if necessary, powders such as alloying element powder and master alloy powder can be used. Here, examples of alloying elements that can be contained in the alloying element powder and master alloy powder include at least one selected from the group consisting of copper, nickel, carbon, chromium, molybdenum, sulfur, manganese, nitrogen, titanium, zirconium, niobium, and phosphorus. When producing an iron alloy green compact or sintered body, the mass ratio of metals in the raw powder can be iron:alloying element=100:0 to 50:50, or even 100:0 to 70:30. Alternatively, when producing an iron-based green compact made of pure molybdenum or a molybdenum alloy, the raw powder may be pure molybdenum powder, and further, if necessary, powders such as alloying element powder and master alloy powder may be used. Here, examples of alloying elements that may be contained in the alloying element powder or master alloy powder include at least one selected from the group consisting of titanium, zirconium, tungsten, and copper. When producing a green compact or sintered body made of a molybdenum alloy, the mass ratio of metals in the raw powder may be molybdenum:alloying element=100:0 to 50:50, or even 100:0 to 70:30.
[0038] The average particle size of the raw material powder is preferably 10 μm to 150 μm. By using such relatively fine particles, it is possible to improve the compression density of the green compact after cold isostatic pressing, and further the sintered compact after sintering or hot isostatic pressing. The average particle size refers to the particle size D50 (median size) of the particle size distribution (volume basis) obtained by the laser diffraction scattering method. The raw material powder may be any known powder such as a pulverized powder or an atomized powder.
[0039] By using such raw powder, titanium-based compacts and titanium-based sintered bodies can be manufactured from pure titanium or titanium alloys such as Ti-5Al-1Fe, Ti-5Al-2Fe, Ti-6Al-4V, Ti-6Al-6V-2Sn, Ti-6Al-2Sn-4Zr-2Mo, Ti-6Al-2Sn-4Zr-6Mo, or Ti-10V-2Fe-3Al. In the above, the numbers in front of each alloy metal indicate the content (mass%). For example, "Ti-6Al-4V" indicates a titanium alloy containing 6 mass% Al and 4 mass% V as alloy metals. EXAMPLES
[0040] Next, the method for producing a powder compact according to the present invention was experimentally carried out, and the effects thereof were confirmed, which will be described below. However, the description here is merely for illustrative purposes and is not intended to be limiting.
[0041] (Test Example 1) Based on the modeling data shown in Figure 9, a mold made of polylactic acid (PLA) (Shore D hardness: 83) and a mold made of acrylic resin containing elastomer (Shore D hardness: 34) were printed using a resin 3D printer. The thickness of each part of the mold was 1.0 mm, the inner diameter of the outer cylinder wall was 80 mm, the inner height was 70 mm, and the inner height of the inner cylinder wall was 40 mm. These dimensions were constant, and multiple molds with different outer diameters of the inner cylinder wall within the range of 10 mm to 50 mm were produced and used for testing.
[0042] In Example 1, a cylindrical core material made of silicone rubber (silicone resin) was used as the core material provided in the inner tube wall of the mold. In Example 2, a cylindrical core material made of fluororubber (fluororesin) was used. In Example 3, a cylindrical core material made of chloroprene rubber (chloroprene resin) was used. In Example 4, a silicone sealant (silicone resin) was injected into the inner tube wall and cured to form a cylindrical shape inside the inner tube wall. In Example 5, the core material was made of the same polylactic acid as the mold, and the core material was formed integrally with the inner tube wall of the mold. A mold made of polylactic acid (PLA) was used in Examples 1 to 5. Example 6 was the same as Example 4, except that a mold made of acrylic resin containing elastomer was used. When the uniaxial compression test was carried out on samples of each resin material for the core material as described above, the stress at 20% strain was 0.6 MPa for the silicone rubber of Example 1, 1.6 MPa for the fluororubber of Example 2, and 1.1 MPa for the chloroprene rubber of Example 3. When the silicone sealants of Examples 4 and 6 were subjected to the uniaxial compression test after curing, the stress at 20% strain was approximately the same as that of the silicone rubber of Example 1.
[0043] In Comparative Example 1, a core material made of alumina was used. In Comparative Example 2, a core material made of tungsten carbide was used. In Comparative Example 3, a core material made of carbon steel (S45C) was used. In all of Comparative Examples 1 to 3, a mold made of polylactic acid (PLA) was used. Note that since the core materials used in Comparative Examples 1 to 3 all had high hardness, the uniaxial compression test was not performed.
[0044] In each of the above Examples 1 to 6 and Comparative Examples 1 to 3, a pure titanium HDH powder (titanium content 99.9% by mass, TC-150 manufactured by Toho Tech Co., Ltd.) having an average particle size of 80 μm was filled into a mold as a raw material powder, and cold isostatic pressing was performed for 1 minute at 490 MPa. After cold isostatic pressing, the mold and core material together with the raw material powder inside were heated to 100° C. in an electric furnace, and the mold was peeled off with pliers or the like to obtain a titanium-based green compact.
[0045] In all of Examples 1 to 6 and Comparative Examples 1 to 3, the raw material powder was solidified by cold isostatic pressing, and a titanium-based green compact could be produced.
[0046] In addition, the surface of the titanium-based powder compact obtained by cold isostatic pressing that was located on the annular wall side of the mold was visually inspected. The results are shown in Table 1 as to whether or not the surface portion near the inner circumference side, which is the core material side, was elevated compared to the surface portion on the outer circumference side.
[0047] [Table 1]
[0048] As can be seen from Table 1, no protuberances were observed in Examples 1 to 6, whereas protuberances were observed in Comparative Examples 1 to 3.
[0049] In addition, after cold isostatic pressing and before heating in an electric furnace, it was also confirmed whether the core material could be easily removed from the recesses of the titanium-based powder compact. The results are shown in Table 2. In Table 2, the number of times that the core material could be easily removed out of two or three attempts to manufacture titanium-based powder compacts is shown as a fraction.
[0050] [Table 2]
[0051] As shown in Table 2, it was possible to easily remove the core material from the silicone rubber of Example 1, the fluororubber of Example 2, and the silicone sealants of Examples 4 and 6. This is thought to be because the core material made of these resins deformed when pulled during removal, which reduced the adhesion between the mold and the core material and reduced the frictional force. On the other hand, it was difficult to remove the core material from the recess of the titanium-based powder compact in the chloroprene rubber of Example 3, the polylactic acid integrated with the mold of Example 5, and the materials containing metal of Comparative Examples 1 to 3. It is considered that removal was difficult in Comparative Examples 1 to 3 because the core material was hard and did not deform during removal, resulting in increased friction. In Examples 3 and 5, the core material was torn off during removal, making removal difficult.
[0052] (Test Example 2) A titanium-based compact 101 having a complex shape as shown in FIG. 10 was manufactured. This titanium-based compact 101 has an overall annular shape with an outer contour shape in a cross section perpendicular to the central axis being a nearly regular octagon, and a similar cross section of the central recess 102 has a shape in which six semicircular recesses 103 are formed at equal intervals around the circular periphery toward the outer periphery. A rectangular parallelepiped protrusion 104 is formed on the outer periphery corresponding to one side of the regular octagon of the outer contour shape described above, extending from the outer periphery to the outer periphery. Pure titanium HDH powder with an average particle size of 80 μm (titanium content 99.9% by mass, TC-150 manufactured by Toho Tech Co., Ltd.) was filled into the mold as raw material powder from the portion where the protrusion 104 was to be formed.
[0053] The mold used to manufacture the titanium-based powder compact 101 was made of polylactic acid (PLA) using a resin 3D printer, and had a Shore D hardness of 83. The mold corresponding to the shape of the titanium-based powder compact 101 had a side length of 55 mm of the regular octagon in the cross section of the outer cylinder wall, a height of 30.5 mm along the central axis of the outer cylinder wall, and dimensions of the portion corresponding to the protrusion 104 were 25 mm long and 25 mm wide.
[0054] The inner cylinder wall of the mold had six recesses, each having a diameter of 4.6 mm and a substantially semicircular cross section, formed at equal intervals in the circumferential direction on the outer surface of a cylinder having an outer diameter of 31.7 mm, corresponding to the recessed portion 103. The core material disposed within the inner cylinder wall to form the recesses 102 was made of silicone sealant.
[0055] Since it was possible to manufacture the titanium-based powder compact 101 shown in FIG. 10 using such a mold and core material, it was found that this invention can successfully manufacture titanium-based powder compacts even with complex shapes.
[0056] (Test Example 3) The conditions for all of Examples 7 to 9 were the same as those for Example 4 of Test Example 1, except that the material of the raw material powder was changed to produce a Ti-6Al-4V (titanium 64 alloy) green compact in Example 7, a pure iron (Fe) green compact in Example 8, and a pure molybdenum (Mo) green compact in Example 9. In Examples 7 to 9, a mold with an outer diameter of an inner cylinder wall portion of 10 mm was used.
[0057] As a result, there was no protrusion in the surface portion near the inner periphery (core material side) of the surface located on the annular wall side of the mold in any of the powder compacts in Examples 7 to 9. This shows that even in powder compacts made of materials other than pure titanium, the occurrence of protrusions on the powder compact surface near the core material can be suppressed. [Explanation of symbols]
[0058] 1, 21, 41 Mold 2, 22, 42 Molding space 3, 23, 43 Outer cylinder wall 4, 24, 44 Annular wall 44a hole 5 Inner cylinder wall 6 Disk-shaped member 11, 31, 51, 71 Core material 61, 81, 91, 101 Titanium-based compacts 62, 82, 92, 102 recess 83 Ridge 103 Depression 104 Projection
Claims
1. 1. A method for producing a metal powder compact having a recess, comprising the steps of: The method includes a step of cold isostatically pressing a raw material powder filled in a resin mold in a state where a resin core material having a shape corresponding to the recess is positioned at a location of the resin mold corresponding to the recess, As the core material, a core material made of a resin material having a stress of 0.3 MPa to 3.5 MPa when the strain is 20% in a uniaxial compression test is used, performing the cold isostatic pressing in a state in which the core material, which is a separate member from the mold, is disposed at a portion of the mold corresponding to the recess, with a wall portion of the mold being sandwiched between the core material and the raw material powder; The method for producing a powder compact comprises producing a titanium-based powder compact made of titanium or a titanium alloy as the powder compact.
2. The method for producing a powder compact according to claim 1 , wherein the core material comprises at least one selected from the group consisting of a silicone resin and a fluororesin.
3. 3. The method for producing a green compact according to claim 1, wherein the mold is made of a thermoplastic resin having a Shore D hardness in the range of 30 to 120.
4. The method for producing a powder compact according to any one of claims 1 to 3, wherein the recess is a non-through depression.
5. A method for producing a green compact described in any one of claims 1 to 4, wherein the pressure applied to the raw material powder by the cold isostatic pressing is 200 MPa or more.
6. A method for producing a sintered body, comprising the steps of: A method for producing a sintered body, comprising a step of sintering and / or hot isostatic pressing a powder compact produced by the method for producing a powder compact according to any one of claims 1 to 5.
Citation Information
Patent Citations
Manufacture of sintered titanium alloy
JP1994033165A
Powder press molding method by uniformly high pressure and rubber mold for powder press molding
JP1996300195A
CIP molding method
JP1997323308A
Method for manufacturing green compact, sintered- titanium valve lifter and its surface-treating method
JP2001131605A
Method for producing powder molding
JP2003305593A